2009
DOI: 10.1177/154193120905300439
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Likelihood Alarm Technology and False-Alarm vs. Miss Prone Automation on Decision Making

Abstract: Past research concerning decision support tools has primarily focused on either false-alarm prone (FP) or miss-prone (MP) automation. Some studies have explored performance disparities of binary versus likelihood alarm technology (BAT vs. LAT) but only in FP automation. The goal of this study was to explore differential effects of alarm technology and FP vs. MP automation on human decision-making accuracy. Onehundred university students performed a low-fidelity uninhabited aerial vehicle flight simulation, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similar to past research (Bustamante, 2008;Clark & Bustamante, 2008;Clark, et al, 2010), the findings in this study provide further support for the benefit of three-state alarms within false alarm prone systems. Findings also showed the benefit of three-state alarms in providing additional diagnostic information to assist operators in diagnosing faults that may have misleading indicators.…”
Section: Resultssupporting
confidence: 78%
“…Similar to past research (Bustamante, 2008;Clark & Bustamante, 2008;Clark, et al, 2010), the findings in this study provide further support for the benefit of three-state alarms within false alarm prone systems. Findings also showed the benefit of three-state alarms in providing additional diagnostic information to assist operators in diagnosing faults that may have misleading indicators.…”
Section: Resultssupporting
confidence: 78%
“…The MSB and SGTR faults were used in this study as illustrative purposes and do not represent the actual frequency that nuclear power plant operators encounter them, which is extremely rare. This task's design is consistent with prior research (Clark, Ingebritsen, & Bustamante, 2010). Participants first monitored alarm advisories for the masking fault, wherein participants decided to ignore or acknowledge the advisory (see Figure 2).…”
Section: Alarm Monitoring Taskmentioning
confidence: 51%
“…In contrast to BASs, LASs have more than one threshold for emitting various alerts, which then differ in their PPV and therefore inform the operator about the relative likelihood of an underlying critical event. Compared to control conditions with classical BASs, LASs were found to improve decision-making and performance in terms of accuracy (e.g., Clark, Peyton, & Bustamante, 2009;Ragsdale, Dyre, & Boring, 2012;, particularly under high-workload conditions and for low base rates (Bustamante 2005(Bustamante , 2008Clark & Bustamante, 2008). Moreover, it has been shown that LASs are especially useful to improve proper responding to alerts in case that the validity of an alert cannot be easily verified towards other available information .…”
Section: Likelihood Alarm Systemsmentioning
confidence: 99%
“…The common procedure of designing a LAS is keeping the initial low threshold of a typical liberal BAS, which separates non-alerts from alerts, but grading the alert level further by adding (at least) one additional threshold (Bustamante 2005(Bustamante , 2008Clark & Bustamante 2008;Clark et al, 2009;Clark, Ingebritsen, & Bustamante, 2010;Ragsdale et al, 2012;Vargas & Bustamante 2011;Wiczorek, 2017;, Wiczorek, Manzey, & Zirk, 2014. Most common are LASs with two thresholds which consist of three stages (3-LAS) as depicted in Figure 1.…”
Section: Likelihood Alarm Systemsmentioning
confidence: 99%